2021
DOI: 10.1080/10942912.2021.1876087
|View full text |Cite
|
Sign up to set email alerts
|

Proteinaceous α-amylase inhibitors: purification, detection methods, types and mechanisms

Abstract: α-Amylase is abundant in plants and animals. α-Amylase inhibitors can reduce endogenous α-amylase activity, playing an essential role in agricultural pest control, and preventing and treating human disease. In the agricultural field, α-Amylase inhibitors can restrict pest that relies on the starch of crops. Acarbose is an α-amylase inhibitor used to treat diabetes. Some αamylase inhibitors are represented by antinutritional factors, while others are proteinaceous. Depending on their structures and sources, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…The soluble proteinaceous α-AIs identified were consistent with findings in the research of Salt, Robertson, Jenkins, Mulholland, and Mills (2005). All proteinaceous α-AIs found in wheat flour extracts were categorised as cereal type or CM type (inhibitors found in chloroform/methanol extracts of wheat) α-AIs, expect the α-amylase/subtilisin inhibitor which was classified as a Kunitz type (H. Li, Zhou, Zhang, Fu, Ying, & Liu, 2021;Svensson et al, 2004).…”
Section: Aqueous Wheat Flours Extracts Are Capable Of Reducing the Di...supporting
confidence: 84%
See 2 more Smart Citations
“…The soluble proteinaceous α-AIs identified were consistent with findings in the research of Salt, Robertson, Jenkins, Mulholland, and Mills (2005). All proteinaceous α-AIs found in wheat flour extracts were categorised as cereal type or CM type (inhibitors found in chloroform/methanol extracts of wheat) α-AIs, expect the α-amylase/subtilisin inhibitor which was classified as a Kunitz type (H. Li, Zhou, Zhang, Fu, Ying, & Liu, 2021;Svensson et al, 2004).…”
Section: Aqueous Wheat Flours Extracts Are Capable Of Reducing the Di...supporting
confidence: 84%
“…The Kunitz type inhibitor - α-amylase/subtilisin inhibitor was widely found in cereals including barley, rice and wheat. Barley α-amylase/subtilisin inhibitor was the most studied which had been reported to specifically inhibits barley α-amylase 2 (H. Li et al, 2021; Svensson et al, 2004). The wheat α-amylase/subtilisin inhibitor has not been well studied, and it was reported to have 92% similarity to barley α-amylase/subtilisin inhibitor in amino acid sequences (Franco et al, 2004; Wisessing & Choowongkomon, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the α-amylase inhibitory effects of neochlorogenic acid and vanillic acid were significantly higher than those of the three phenolic acids reported above but were lower than that of acarbose (85.67%). An alpha-amylase inhibitor of acarbose is the dominant drug in the field of diabetes, but it also has some toxicity and side effects, such as diarrhea, abdominal pain, and abdominal discomfort ( 47 ). Therefore, it is necessary to search for α-amylase inhibitors in natural products.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, α‐amylase represents the crucial step in the initiation of the process of digestion and absorption of dietary polysaccharides (Tangphatsornruang, Naconsie, Thammarongtham, & Narangajavana, 2005). Therefore it can be the target for specific enzyme inhibitors, allowing to reduce the rate of carbohydrate absorption, the real energetic intake after a meal, and the subsequent glycemic peak (de Sales et al, 2012; Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%